Meticillin-resistant Staphylococcus aureus and meticillin-susceptible Staphylococcus aureus screening in a cohort of haemodialysis patients: carriage, demographics and outcomes. Issue 1 (May 2015) - Price, A.; Sarween, N.; Gupta, I.; Baharani, J.
Summary Background Patients on haemodialysis are vulnerable to colonization with Staphylococcus aureus due to frequent hospital contact, indwelling devices, and impaired immunity. Additionally colonization is associated with increased risk of infection. Aim To determine the prevalence of both meticillin-resistant S. aureus (MRSA) and meticillin-susceptible S. aureus (MSSA) carriage in our haemodialysis cohort and to identify any risk factors predisposing to carriage, recolonization, or persistent carriage following a decolonization programme. Methods All haemodialysis patients screened for S. aureus carriage between June 2009 and May 2011 were retrospectively followed up for 18 months using hospital electronic records. Statistical analysis was performed using IBM SPSS version 19. Findings Out of 578 patients screened, 288 patients (49%) had at least one positive swab (10% MRSA, 90% MSSA). Of these patients, 265 completed a course of decolonization therapy following which 36% successfully eradicated (eradicators) and 64% did not (non-eradicators). There was no statistically significant difference in patient demography, type of vascular access, 18-month patient mortality, or number of hospital admissions between the two groups. Those who failed to eradicate were more likely to have had an episode of S. aureus bacteraemia within the study period compared to those who successfully decolonized (P = 0.003). Conclusion Half of our haemodialysis cohort was colonized with S. aureus at any one time over an 18-month period. Following decolonization, one-third of patients remained successfully eradicated for 18 months. Non-eradicators have an increased risk of bacteraemia, which is associated with poor mortality. We would recommend routine screening and aggressive attempts to decolonize.